Application of Storytelling in Organizations: A Review of Latest Literature with Implications for India - Mendonca, Valerie (Prabandhan: Indian Journal of Management, 2015)
Storytelling is one of the ancient art forms of communication. Organizational Storytelling is one of the latest management trends, and there has been an increased rise in storytelling research as well as consultation. The application of storytelling lends itself to the study of the latest research in this area. There has been a vast number of studies documenting organizational stories as well as vouching about the effectiveness of storytelling. Studies in organizational stories date back to the early 1980s. Subsequent reviews have tried to analyze or categorize organizational stories. This paper focused more on the application of stories in organizations from a practical point of view. The objective of the paper was to understand the current use of stories in the workplace and recommend its use according to Indian work settings. This paper attempted to review the latest research on organizational storytelling with suggestions to its application in Indian organizations.